The Way of Kata in Kodokan Judo - Jones, Llyr C.; Hanon, Michael J. (Revista de Artes Marciales Asiáticas, 2012)
This article presents a “deep dive” into the formal exercises (katas) of Kodokan judo. Specifically, it has two objectives: (i) to explain the purpose of kata in judo, and (ii) to critically evaluate the concept of kata championships. To achieve these objectives, we offer the authors’ personal comments, observations from rare Japanese source material, as well as insight into the thinking of world-renowned judo experts. We conclude that the concept of kata championships is fundamentally flawed and also damaging kata training.